Asymptotic estimates for the solution of stochastic differential equations driven By G-Brownian motion. Issue 12 (10th September 2018) - Wei, Wei; Zhang, Miao; Luo, Peng
Abstract: In this paper, we give four results of asymptotic estimates for the solution of stochastic differential equations driven by G-Brownian motion, which have different convergence rates under different assumptions. One of them can be considered as a Law of the Iterated Logarithm of the solution of G-SDEs under nonlinear conditions.